DESIGN OPTIMIZATION OF RADIAL-AXIAL FLOW TYPE F WATER TURBINE RUNNER - (NIM : 23106017); Pembimbing : Dr.Priyono Sutikno, GUSRIWANDI
This rsearch is aimed ti fined the optimum shape of leading and trailing edge of runner of radial-axial flow of water turbine by comparing computer simulation result of three turbine where the runner of them are designed at same specific velocity. In this research is used an alternative way, namely by using an parabolic equation to replace graphical-analytical methods in choosing leading and trailing edge, so in a short time it can be found a few leading and trailing shapes. By considering velocity variation on streamlines in meridional plane, three couple shape of leading and trailing edge of runners are chooseb to build three turbines.